2019
DOI: 10.30607/kvj.599782
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Determination with Detection of Serum Specific IgE in Dogs with Atopic Dermatitis from Samsun and Vicinity

Abstract: It is aimed to detect allergen determination via serum specific immunoglobulin E (IgE) for the first time in dogs diagnosed as Atopic Dermatitis (AD) from Samsun and vicinity within this present study. Twenty one dogs with different age, breed and gender diagnosed with AD based up on the Favrot's criteria. Serum samples of the dogs were analyzed by detection of serum specific IgE for determination of 20 different allergens. The effects of gender, age and the feeding routes for those 20 different allergens sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Previous studies on canines with AD (6, 40, 43, 44) have reported that the causative allergens associated with the etiology of the disease include house dust mite 1, house dust mite 2 (6,40,43,44), flea mite (40), food mite (6,44), flour mite, plant mite, rye pollen (6), grass pollen (6,43), and banana pollen (43). Upon allergen testing with serum-specific IgE, the present study identified the most prevalent allergens to be house mites type 1, house mites type 2, flea mites, plant and flour mites, pollen of hornbeam family trees, and food parasites (Lepidoglyphus).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous studies on canines with AD (6, 40, 43, 44) have reported that the causative allergens associated with the etiology of the disease include house dust mite 1, house dust mite 2 (6,40,43,44), flea mite (40), food mite (6,44), flour mite, plant mite, rye pollen (6), grass pollen (6,43), and banana pollen (43). Upon allergen testing with serum-specific IgE, the present study identified the most prevalent allergens to be house mites type 1, house mites type 2, flea mites, plant and flour mites, pollen of hornbeam family trees, and food parasites (Lepidoglyphus).…”
Section: Resultsmentioning
confidence: 96%
“…The severity of pruritus in skin allergic reactions is important with regard to the occurrence of primary skin lesions (erythema, papule, and pustule) and secondary skin lesions (epidermal collarettes, crusting, peeling, alopecia, hyperpigmentation, and lichenification) during the course of the disease (13,19). Mites, lice, and flea infestations and allergens, such as lawn and grass pollen, have been reported to play a significant role in the etiology of AD (6,19,30,41,66,67). Various tests (allergen testing with serumspecific IgE and intradermal skin testing) can identify causative allergens involved in the etiology of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ö. Barili and D. Pekmezci (2019) show that in atopic dermatitis in dogs, specific Ig E levels are above the threshold. They note that genetic factors affect the level of Ig E in dogs.…”
Section: Table 5 Biochemical Parameters In the Blood Serum Of Dogs Un...mentioning
confidence: 95%